Environmental applications of reduced sulfur species and composites in transformation and detoxification of contaminants. Issue 6 (December 2021) - Rahim, Hafeez Ur; Qaswar, Muhammad; Wang, Maolin; Jing, Xudong; Cai, Xiyuan
Abstract: The outspread distributions of xenobiotic organic compounds (XOCs) and heavy metal ions as potential pollutants in the environmental matrices have recently been challenging for human health. The efficient removal of these pollutants is one of the most crucial issues from an environmental perspective. Numerous studies have been steadfast in investigating the potential role of sulfur-based materials in the remediation of XOCs and heavy metal ions present in soils, sediments, surfaces, and underground wastewater. In the era of sulfur-based materials, reduced sulfur species and their composites stand out as a promising alternative material with versatile surface functionalities and active sites, which allowed them to react with a wide range of pollutants. This review aims to critically evaluate the potential of specific reduced sulfur species and their composites, such as thiosulfate (S2 O3 2- ), and various sulfides (H2 S, Na2 S, FeS, CaSx, MoS2, and ZnS) in the reductive transformation/degradation of XOCs and immobilization of heavy metal ions. Research shows that reduced sulfur species and composites efficiently degrade and detoxify halogenated pesticides (e.g., chloroacetanilide herbicides and halogenated alkane fumigants) through SN 2 nucleophilic substitution and reductive dehalogenation. Moreover, these species/materials find their applications in soil and water remediation of heavy metal ions (e.g., Cd 2+, Cr 2+, Hg 2+, Zn 2+, and Cu 2+ ) through chemical precipitations, surface complexation, adsorption, ion exchange, and reduction. The underlying reaction mechanisms for both XOCs and heavy metal ions are discussed. In addition, future research recommendations regarding reduced sulfur species-based materials improvement and their potential applications in environmental remediation are proposed. Graphical Abstract: ga1 Highlights: Review on reduced sulfur species & composites for pollutants removal is presented. The underlying mechanisms of reduced sulfur materials are interpreted. Several sulfur-based materials have been used for pollutants removal. Reduced sulfur species and composites efficiently removed pollutants. Challenges and possible perspectives on reduced sulfur materials have been discussed.